Mystery Cults in Visual Representation in Graeco-Roman Antiquity - Belayche, Nicole,; Massa, Francesco, (Religions in the Graeco-Roman World ;, 2021)
Mystery Cults in Visual Representation in Graeco-Roman Antiquity aims to fill a gap in the study of mystery cults in Graeco-Roman Antiquity by focusing on images for investigating their ritual praxis. Nicole Belayche and Francesco Massa have gathered experts on visual language in order to illuminate cultic rituals renowned for both their "mysteries" and their images. This book tackles three interrelated questions. Focusing on the cult of Dionysus, it analyses whether, and how, images are used to depict mystery cults. The relationship between historiography and images of mystery cults is considered with a focus on the Mithraic and Isiac cults. Finally, turning to the cults of Dionysus and the Mother of the Gods, this work shows how depictions of specific cultic objects succeed in expressing mystery cults.